Anaerobic co-digestion in a liquid recirculation pilot-scale reactor: Thermal and hydraulic study - Mohammed El Ibrahimi; Ismail Khay; Anas El Maakoul; Mohamed Ould Moussa; Abdelwahed Barkaoui; Mohamed Bakhouya (Energy Reports, 2020)
Morocco's economy relies heavily on agriculture, which leads to an abundance in the availability of both vegetal and animal waste. Different treatment and disposal methods have been proposed to produce energy. Anaerobic digestion, being one of them, is being extensively used due to its lower environmental impact. In this paper, we are studying a wet, mesophilic, anaerobic co-digestion of animal and vegetable waste, using a pilot-scale anaerobic digester with liquid recirculation and immersed solid waste. In fact, this study could be divided into two main parts, the first one being a thermal study aiming to investigate the influence of the liquid recirculation's flow rate and the substrate's presence/absence on the heat transfer to the digester, and a second part presents a Computational Fluid Dynamics analysis (CFD) using FLUENT software tool, allowing a better understanding of the fluid's behavior inside the digester. Simulations have been conducted and results show that a higher recirculation flow rate increases heat delivery to the effluent (from 0.18 to 0.66 kWh) but has a negative impact on pressure drop (from 429 to 1937.41 Pa). It was also observed that the liquid percolated more easily and through a larger portion of the waste at lower flow rates.
Keywords: 330; Anaerobic digestion; Biogas; Computational Fluid Dynamics analysis; Liquid recirculation; Thermohydraulic study